Tantangan Konservasi Alam Di Kalimantan Timur Di Tengah Eksploitasi Hutan, 1967-1998 - Muhammad Khoiruddin (Pendidikan IPS FKIP ULM, 2023)
The nature conservation in East Kalimantan in 1967-1998 has been the focused of this study. After the 1967 to 1998 is the period of the massive conservation of Kalimantan natural forest, especially in the East Kalimantan that destroys natural forest extensively. The damage does not only affect the forest cover, but also threaten the habitat of various important animals. In the middle of the forest exploitation, the East Kalimantan nature conservation has been growing since the late 1970s. The objective of the research is explaining the development of East Kalimantan nature conservation area and its challenges in the vortex of forest exploitation. The historical approach is applied to compile and elaborate problems historically consisting of four stages, namely heuristics, criticism, interpretation, and historiography. The results show the New Order economic development policies significantly affect the emergence of threats to nature conservation in East Kalimantan. In the late 1970s, the growth of conservation area in the East Kalimantan natural forest was lagging due to the previous forest exploitation that ran for decade since 1967. Continuous forest exploitation since 1967 has fragmented conservation areas and created various threats that bear challenges to nature conservation efforts. The emerging threats include conflicts of flora and fauna, encroachment and tenurial conflicts, as well as illegal logging and mining.